Relationship between the impact peak force and lower extremity kinematics during treadmill running - Ryu, J.-S.; Park, S.-K. (Korean Journal of Sport Biomechanics, 2018)
Objective: The aims of this study were to determine the impact peak force and kinematic variables in running speed and investigate the relationship between them.